2013
DOI: 10.1590/s0102-09352013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Swimmer syndrome affecting an entire litter of kittens

Abstract: Swimmer syndrome is a developmental abnormality characterized by a delay in the ability to walk and move about and is manifested in newborns between 15 and 20 days of age. These animals exhibit constant coxofemoral articulation abduction, and their pelvic limbs move caudally and laterally. This case reports a litter of three crossbreeds kittens (26 days old) with swimmer syndrome. Each animal was treated with physical therapy and shackle bandages that kept their pelvic limbs bent and close to the body. After s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Orthopedic, nutritional, neurological, genetic, and environmental factors have been discussed as causes of this syndrome [ 1 , 2 , 4 – 8 ], but the exact mechanisms of this syndrome are still unclear. Diagnostic criteria and general treatments have not been established, but treatments such as physiotherapy, bandages, and massage were suggested to yield good progress in some reports [ 2 , 4 7 , 9 ]. According to these reports, the prognosis varies depending on the severity, from cases leading to dyspnea and aspiration pneumonia to those that resolve themselves spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic, nutritional, neurological, genetic, and environmental factors have been discussed as causes of this syndrome [ 1 , 2 , 4 – 8 ], but the exact mechanisms of this syndrome are still unclear. Diagnostic criteria and general treatments have not been established, but treatments such as physiotherapy, bandages, and massage were suggested to yield good progress in some reports [ 2 , 4 7 , 9 ]. According to these reports, the prognosis varies depending on the severity, from cases leading to dyspnea and aspiration pneumonia to those that resolve themselves spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…A etiologia é incerta e alguns autores sugerem que há envolvimento de fatores genéticos, pois filhotes com a afecção eram pertencentes a mesma ninhada e/ou provenientes de cruzamentos consanguíneos (Cardilli et al, 2013;Paschoal et al, 2003). No entanto, Kathmann et al (2001), reconhece que um filhote pode ser acometido isoladamente, da mesma forma que no presente relato.…”
Section: Discussionunclassified
“…Orthopedic, nutritional, neurological, genetic, and environmental factors have been discussed as causes of this syndrome [1,2,[4][5][6][7][8], but the exact mechanisms of this syndrome are still unclear. Diagnostic criteria and general treatments have not been established, but treatments such as physiotherapy, bandages, and massage were suggested to yield good progress in some reports [2,[4][5][6][7]9]. According to these reports, the prognosis varies depending on the severity, from cases leading to dyspnea and aspiration pneumonia to those that resolve themselves spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that funnel chest is often present [1,3]. Orthopedic, nutritional, neurological, genetic, and environmental factors have been discussed as causes of this syndrome [1,2,[4][5][6][7][8], but the exact mechanisms of this syndrome are still unclear. Diagnostic criteria and general treatments have not been established, but treatments such as physiotherapy, bandages, and massage were suggested to yield good progress in some reports [2,[4][5][6][7]9].…”
Section: Introductionmentioning
confidence: 99%